An investigation on predictors of life satisfaction among the elderly - Eshkoor, Sima Ataollahi; Tengku Abdul Hamid, Tengku Aizan; Chan, Yoke Mun; Shahar, Suzana (International Organization Center of Academic Research, 2015)
In the elderly, the perception of life satisfaction and quality of life is associated with many factors such as healthy life-span, chronic illnesses, expectations and self-perception of ageing. This study aims to determine the effects of different variables including age, employment, cognition, polygamy, ethnicity, debt, marital status, sex differences, intimacy capability, sleep hours, home ownership status, taking salary, educational level, and living with a partner on life satisfaction in the elderly. This study recruited 2322 respondents who were non-institutionalized Malaysian elderly aged 60 years and above. Life satisfaction was measured by asking in general “Are you satisfied with your current life”. The multiple logistic regression analysis was used to predict the effects of susceptible variables on life satisfaction among subjects. Approximately, 90.4 % of respondents reported that they were satisfied with their current life. The results of multiple regression analysis showed that ethnic Malay (odds ratio [OR] = 1.46; p = 0.022), and living with a partner (OR = 2.11; p = 0.011) significantly increased life satisfaction among subjects (p<0.05). Age, sex differences, employment, polygamy, cognition, marital status, educational level, debt, home ownership status, taking salary, intimacy capability and sleep hours were not significant factors for being satisfied in life among respondents (p>0.05). It was concluded that ethnic Malay and living with a partner increased the feeling of life satisfaction among subjects.